2008
DOI: 10.1074/jbc.m803682200
|View full text |Cite
|
Sign up to set email alerts
|

Polypyrimidine Tract-binding Protein (PTB) Differentially Affects Malignancy in a Cell Line-dependent Manner

Abstract: RNA processing is altered during malignant transformation, and expression of the polypyrimidine tract-binding protein (PTB) is often increased in cancer cells. Although some data support that PTB promotes cancer, the functional contribution of PTB to the malignant phenotype remains to be clarified. Here we report that although PTB levels are generally increased in cancer cell lines from multiple origins and in endometrial adenocarcinoma tumors, there appears to be no correlation between PTB levels and disease … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 47 publications
(38 reference statements)
6
58
1
Order By: Relevance
“…Similarly, PTB-1 overexpression has been implicated in tumourigenesis; it is overexpressed in certain cancers (He et al, 2007;Wang et al, 2008) and a reduction in PTB-1 expression in ovarian cancers reduces cell proliferation (He et al, 2007). The data form our study show that a reduction in PTB-1 expression alone in cell lines derived from patients with MM had a dramatic effect on cell proliferation although, interestingly, there was little effect on the control B cells used.…”
mentioning
confidence: 50%
“…Similarly, PTB-1 overexpression has been implicated in tumourigenesis; it is overexpressed in certain cancers (He et al, 2007;Wang et al, 2008) and a reduction in PTB-1 expression in ovarian cancers reduces cell proliferation (He et al, 2007). The data form our study show that a reduction in PTB-1 expression alone in cell lines derived from patients with MM had a dramatic effect on cell proliferation although, interestingly, there was little effect on the control B cells used.…”
mentioning
confidence: 50%
“…Furthermore, PTB KD decreases breast and ovarian tumor cell proliferation, anchorage-independent growth, and invasiveness in vitro (He et al 2007(He et al , 2014, and is accompanied by an increased ratio of PKM1 versus PKM2 isoform and increased oxygen consumption (He et al 2014). PTB overexpression also enhances anchorage-dependent growth of immortalized human mammary epithelial cells (HMECs) (He et al 2014); however, overexpression of PTB alone is not sufficient to transform murine fibroblasts (Wang et al 2008). Together, these results suggest that PTB plays a role in breast tumorigenesis.…”
Section: Hnrnpk-heterogeneous Nuclear Ribonucleoprotein Kmentioning
confidence: 77%
“…PTB controls alternative splicing of target genes, such as pyruvate kinase PKM2 (Clower et al 2010), fibroblast growth factor receptor-1α-exon FGFR-1 (Jin et al 2000), and multidrug resistance protein 1 (MRP1), which contributes to the drug-resistance phenotype associated with many cancers (He et al 2004). PTB levels are elevated in cancer cell lines, as well as endometrial tumor tissues, compared to normal tissues, although no correlation was observed between PTB expression and tumor grading (Wang et al 2008). PTB is also overexpressed in most ovarian tumors, compared with matched normal tissue, and its overexpression is associated with an increased number of expressed MRP1 spliced isoforms (He et al 2004(He et al , 2007.…”
Section: Hnrnpk-heterogeneous Nuclear Ribonucleoprotein Kmentioning
confidence: 99%
“…However, one cannot exclude this might be a specific cell type effect. 24 Cardiac glycosides have been shown previously to be potent inhibitors, at the level of translation, of the expression of the tumor suppressor p53 as well as the hypoxiainducible transcription factor 1 (HIF-1) in hypoxic tumor cells. 25,26 It was shown that digoxin very potently inhibits HIF-1 mRNA translation and affects mouse xenograft tumor growth associated with modest effects on global protein synthesis.…”
Section: Discussionmentioning
confidence: 99%